CO2 capture 2-amino-2-methyl-1-propanol/piperazine degradation. Comparison of BECCS and cement production - Randi Neerup; Isaac A. Løge; Gry A. Bachson; Magdalena Gautsch; Kalle L. Øbro; Nomiki Kottaki; Pantelis Bountzis; Maria Dimitriadi; Søren Jensen; Jakob L. Karlsson; Kristian R.K. Krum; Søren Christensen; et al. (Journal of Environmental Chemical Engineering, 2026)

Pilot study of a novel electrochemical approach for NOx removal from flue gas - Maria Dimitriadi; Sebastian Borgquist; Ward Peeters; Sebastian Nis Bay Villadsen; Christian Warm; Jens Abildskov; Philip Loldrup Fosbøl (Chemical Engineering Journal, 2026)

Assessing the limits: citizen science data accuracy in underwater monitoring - Charalampos Dimitriadis; Katerina Konsta; Melih Ertan Çinar; Alper Doğan; Vasilis Gerovasileiou; Giulia Gatti; Laure Thierry de Ville d’Avray; Maria Sini; Stelios Katsanevakis; Antonios D. Mazaris; Drosos Koutsoubas (Biodiversity and Conservation, 2026)

Pilot-scale CO 2 capture in a cement plant with CESAR1: Leveraging absorber intercooling and cold-feed heat-integration to lower the SRD - Isaac Appelquist Løge; Can Demir; Sai Hema Bhavya Vinjarapu; Randi Neerup; Ebbe Hauge Jensen; Jens Kristian Jørsboe; Maria Dimitriadi; Halil Halilov; Carsten Fritzner Frøstrup; Istvan Gyorbiro; Nomiki Kottaki; Asams Nelliparambil Jayan; et al. (Chemical Engineering Journal, 2025)

Process configurations for emission control: CESAR1 emission behavior in biomass combustion gas treatment - Maria Dimitriadi; Christina Andersen; Isaac Appelquist Løge; Randi Neerup; Søren Jensen; Jakob Lindkvist Karlsson; Pantelis Bountzis; Nomiki Kottaki; Frantz Bræstrup; Kristian Røhe Kongst Krum; Søren Christensen; Sebastian Nis Bay Villadsen; et al. (Chemical Engineering Journal, 2025)

Distinct immune responses confer partial resistance to Fusarium wilt in tomato landraces - Antonis Tzionis; Giorgos Artymatas; Angelos C. Kyratzis; Stavroula Dimitriadi; Maria-Dimitra Tsolakidou; Iakovos S. Pantelides (Planta, 2025)
Main Conclusion Cypriot tomato landraces exhibit partial resistance to Fusarium wilt through distinct jasmonic and salicylic acid-mediated immune responses, offering promising genetic resources for breeding durable tomato cultivars. Abstract Fusarium wilt, caused by Fusarium oxysporum f. sp. lycopersici ( Fol ), is a major constraint on global tomato ( Solanum lycopersicum ) production, with few sustainable control measures available. This study assessed six Cypriot tomato landraces for resistance to Fol and explored the mechanisms underlying their defense. Pathogenicity assays under controlled growth conditions identified two landraces, ARI00732 and ARI00733, with partial resistance and improved growth performance compared to the susceptible cultivar Ailsa Craig. A second pathogenicity trial using sterilized and non-sterilized soils revealed no significant contribution of soil microbiota, suggesting intrinsic plant defenses as the primary mechanism. In vitro assays showed that root exudates from these landraces neither inhibited Fol growth nor altered fungal chemotropism. Gene expression analysis revealed distinct defense strategies: ARI00732 displayed strong induction of jasmonic acid (JA)-responsive genes ( MYC2 , LoxD , PDF1.2 ), whereas ARI00733 upregulated salicylic acid (SA)-associated Pti5 gene and the antioxidant defense gene APX1 . These findings demonstrate that complementary JA- and SA-mediated pathways contribute to resistance. This work highlights the potential of tomato landraces as a source of durable resistance traits and provides a foundation for breeding programs targeting Fusarium wilt.

Pilot-scale CO2 capture in a cement plant with CESAR1: Higher stripper pressure reduces energy demand and compression work but increases solvent degradation - Isaac Appelquist Løge; Can Demir; Sai Hema Bhavya Vinjarapu; Randi Neerup; Ebbe Hauge Jensen; Jens Kristian Jørsboe; Maria Dimitriadi; Vanja Buvik; Halil Halilov; Carsten Fritzner Frøstrup; Istvan Gyorbiro; Nomiki Kottaki; et al. (Chemical Engineering Journal, 2025)

Fosfomycin for the treatment of patients with bacterial prostatitis: a systematic review - Dimitrios S. Kontogiannis; Maria Eleni Agoranou; Fotios Dimitriadis; Vassilios M. Skouteris; Matthew E. Falagas (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

CO2 capture pilot campaign: Understanding solvent degradation of CESAR1 in cement plant operations - Randi Neerup; Kalle L. Øbro; Isaac A. Løge; Nomiki Kottaki; Carsten F. Frøstrup; Istvan Gyorbiro; Maria Dimitriadi; Halil Halilov; Søren Jensen; Jakob L. Karlsson; Philip L. Fosbøl (Chemical Engineering Journal, 2025)

Pilot-scale CO2 capture in a cement plant with CESAR1: Comparative analysis of specific reboiler duty across advanced process configurations - Isaac Appelquist Løge; Can Demir; Sai Hema Bhavya Vinjarapu; Randi Neerup; Ebbe Hauge Jensen; Jens Kristian Jørsboe; Maria Dimitriadi; Halil Halilov; Carsten Fritzner Frøstrup; Istvan Gyorbiro; Nomiki Kottaki; Asams Nelliparambil Jayan; et al. (Chemical Engineering Journal, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Genotoxicity and metabolic changes induced via ingestion of virgin and UV-aged polyethylene microplastics by the freshwater fish Perca fluviatilis - Ioannis Sampsonidis; Kostantina Michailidou; Kalliopi Spritinoudi; Anastasia Dimitriadi; Nina Maria Ainali; Dimitra C. Bobori; Dimitra A. Lambropoulou; George Z. Kyzas; Dimitrios N. Bikiaris; Stavros Kalogiannis (Chemosphere, 2024)

The Ionian Sea in the eastern Mediterranean: Critical year-round habitats for sea turtles and diverse marine megafauna, spanning all life stages and genders - Maria Papazekou; Charalampos Dimitriadis; Dimitra Dalla; Chanel M. Comis; Efthimios Spinos; Christopher Vavasis; Kadiani Kapellaki; Athanasia Michalopoulou; Anna-Thalassini Valli; Dimitrios Barelos; Spiridon Konstas; Ioannis Selimas; et al. (Ocean & Coastal Management, 2024)

Changes in cardiovascular health and white matter integrity with aerobic exercise, cognitive and combined training in physically inactive healthy late-middle-aged adults: the “Projecte Moviment” randomized controlled trial - Francesca Roig-Coll; Alba Castells-Sánchez; Gemma Monté-Rubio; Rosalía Dacosta-Aguayo; Noemí Lamonja-Vicente; Pere Torán-Monserrat; Guillem Pere; Alberto García-Molina; José Maria Tormos; Maria Teresa Alzamora; Dimitriadis Stavros; Marta Sánchez-Ceron; et al. (European Journal of Applied Physiology, 2024)
Introduction This is a 12-weeks randomized controlled trial examining the effects of aerobic exercise (AE), computerized cognitive training (CCT) and their combination (COMB). We aim to investigate their impact on cardiovascular health and white matter (WM) integrity and how they contribute to the cognitive benefits. Methods 109 participants were recruited and 82 (62% female; age = 58.38 ± 5.47) finished the intervention with > 80% adherence. We report changes in cardiovascular risk factors and WM integrity (fractional anisotropy (FA); mean diffusivity (MD)), how they might be related to changes in physical activity, age and sex, and their potential role as mediators in cognitive improvements. Results A decrease in BMI (SMD = − 0.32, p = 0.039), waist circumference (SMD = − 0.42, p = 0.003) and diastolic blood pressure (DBP) (SMD = − 0.42, p = 0.006) in the AE group and a decrease in BMI (SMD = − 0.34, p = 0.031) and DBP (SMD = − 0.32, p = 0.034) in the COMB group compared to the waitlist control group was observed. We also found decreased global MD in the CCT group (SMD = − 0.34; p = 0.032) and significant intervention-related changes in FA and MD in the frontal and temporal lobes in the COMB group. Conclusions We found changes in anthropometric measures that suggest initial benefits on cardiovascular health after only 12 weeks of AE and changes in WM microstructure in the CCT and COMB groups. These results add evidence of the clinical relevance of lifestyle interventions and the potential benefits when combining them. Clinical Trial Registration ClinicalTrials.gov NCT031123900.

Intrinsic functional brain connectivity changes following aerobic exercise, computerized cognitive training, and their combination in physically inactive healthy late-middle-aged adults: the Projecte Moviment - Stavros I. Dimitriadis; Alba Castells-Sánchez; Francesca Roig-Coll; Rosalía Dacosta-Aguayo; Noemí Lamonja-Vicente; Pere Torán-Monserrat; Alberto García-Molina; Gemma Monte-Rubio; Chelsea Stillman; Alexandre Perera-Lluna; Maria Mataró (GeroScience, 2023)
Lifestyle interventions have positive neuroprotective effects in aging. However, there are still open questions about how changes in resting-state functional connectivity (rsFC) contribute to cognitive improvements. The Projecte Moviment is a 12-week randomized controlled trial of a multimodal data acquisition protocol that investigated the effects of aerobic exercise (AE), computerized cognitive training (CCT), and their combination (COMB). An initial list of 109 participants was recruited from which a total of 82 participants (62% female; age = 58.38 ± 5.47) finished the intervention with a level of adherence > 80%. Only in the COMB group, we revealed an extended network of 33 connections that involved an increased and decreased rsFC within and between the aDMN/pDMN and a reduced rsFC between the bilateral supplementary motor areas and the right thalamus. No global and especially local rsFC changes due to any intervention mediated the cognitive benefits detected in the AE and COMB groups. Projecte Moviment provides evidence of the clinical relevance of lifestyle interventions and the potential benefits when combining them.

Social-ecological features of set nets small-scale fisheries in the context of Mediterranean marine protected areas - ANTONIO CALÒ; ANTONIO DI FRANCO; CHARALAMPOS DIMITRIADIS; LEA PIACENTINI; PATRICIA VENTURA; ALEXIS PEY; JOSÉ ANTONIO GARCÍA-CHARTON; ERIC CHARBONNEL; VICTOR DECUGIS; FRANCESCO DE FRANCO; IVONI FOURNARI-KONSTANTINIDOU; JOSIPA GRBIN; et al. (Mediterranean Marine Science, 2023)
The small-scale fisheries (SSF) sector has attracted considerable attention over the last decade due to its major importance in sustaining the livelihoods of coastal communities worldwide, poverty alleviation, food security, social wealth and traditions. Despite this importance, quantitative and qualitative information on SSF is still largely lacking and when available, it tends to be scattered or very localized. SSF are also among the very few professional extractive activities generally allowed within Marine Protected Areas (MPAs), and are therefore expected to acquire further momentum in the near future in light of the projected increase of protected marine surface area due to international commitments. However, SSF associated with areas including MPAs may differ from those operating in unprotected contexts with regard to a range of socio-ecological aspects, thus potentially making management strategies currently in force unsuitable, and requiring the development of ad hoc local and regional policies. Here, we assessed the socio-ecological dimension of SSF operating within and around 11 Mediterranean MPAs, in six EU countries, with the aim of identifying relevant patterns that could inform policy and management relative to this fishing sector in view of the forthcoming increase of the marine surface area under protection. To do so, we have adopted a collaborative approach with fishers and combined a photo-sampling survey of 1,292 set net (mainly trammel-nets) fishing operations at landing with 149 semi-structured interviews with fishers, to gather information on features and catches of SSF fleets (e.g. vessel characteristics, gears, catch composition, catch and revenue per unit of effort). Overall, results highlighted: 1) multiple shared features emerging at regional level (i.e. among the 11 study areas), such as the predominant use of set nets, the major contribution of a limited number of species to the overall catch and revenue, the occurrence in the catch of threatened species and/or undersized individuals; 2) a variety of distinctive socio-ecological features differentiating local SSF communities such as the species mainly contributing to catch and revenue, species size distribution and fleet characteristics. In addition to presenting elements to inform common policies and strategies for SSF management in the context of MPAs, our study provides guidance for the development of a standard methodology for the full documentation of SSF in the Mediterranean Sea.

Priorities for Mediterranean marine turtle conservation and management in the face of climate change - Antonios D. Mazaris; Charalampos Dimitriadis; Maria Papazekou; Gail Schofield; Aggeliki Doxa; Anastasia Chatzimentor; Oguz Turkozan; Stelios Katsanevakis; Aphrodite Lioliou; Sara Abalo-Morla; Mustapha Aksissou; Antonella Arcangeli; et al. (Journal of Environmental Management, 2023)

ClimateFish: A Collaborative Database to Track the Abundance of Selected Coastal Fish Species as Candidate Indicators of Climate Change in the Mediterranean Sea - Ernesto Azzurro; Tosca Ballerini; Chryssanthi Antoniadou; Giulia Domizia Aversa; Jamila Ben Souissi; Andrea Blašković; Valentina Cappanera; Marina Chiappi; Maria-Francesca Cinti; Francesco Colloca; Ivan Cvitković; Manuela D’Amen; et al. (Frontiers in Marine Science, 2022)

Pinna nobilis in the Greek seas (NE Mediterranean): on the brink of extinction? - MARIA ZOTOU; PAVLOS GKRANTOUNIS; ELPIDA KARADIMOU; KONSTANTINOS TSIRINTANIS; MARIA SINI; DIMITRIS POURSANIDIS; MARTA AZZOLIN; THANOS DAILIANIS; ELENI KYTINOU; YIANNIS ISSARIS; VASILIS GERAKARIS; MARIA SALOMIDI; et al. (Mediterranean Marine Science, 2020)
The Mediterranean endemic fan mussel Pinna nobilis is suffering an ongoing basin-scale mass mortality event (MME) since 2016. As most Mediterranean populations have collapsed, the species has been declared as Critically Endangered in the IUCN Red List of threatened species. In an effort to track the progress of the MME and provide updated information on the status of the species in the Greek seas, we compiled data collected through dedicated surveys and opportunistic assessments during 2019 and 2020. A total of 14589 fan mussel individuals, of which 81.1% dead, were recorded in 258 site surveys. Of the remaining 2762 live individuals, 256 were juveniles. Two marine areas which still sustain living populations were identified, namely Kalloni Gulf (Lesvos Island), and Laganas Bay (Zakynthos Island). The inner part of Kalloni Gulf appears to maintain the largest surviving population of the species in the eastern Mediterranean, with an abundance estimate of 684000 individuals (95% confidence interval: 322000-1453000). Solitary, potentially resistant, scattered individuals were recorded in several sites. Other previously abundant populations that had been assessed in the past, specifically those of Lake Vouliagmeni (Korinthiakos Gulf), Souda Bay (Crete) and Gera Gulf (Lesvos Island), and which collectively summed up to ~350,000 individuals, have now been wiped out. Our results document the collapse of most P. nobilis populations throughout the Greek seas. The MME has substantially progressed between early 2019 and mid-2020, as indicated by the increase of mortality at sites consecutively monitored multiple times. This work highlights the urgent need for continuous monitoring of surviving populations and calls for the immediate implementation of an effective protection and management strategy that will ensure the persistence of surviving individuals and the production of resistant offspring.

Updating the occurrences of Pterois miles in the Mediterranean Sea, with considerations on thermal boundaries and future range expansion - CHARALAMPOS DIMITRIADIS; MARIKA GALANIDI; ARGYRO ZENETOS; MARIA CORSINI-FOKA; IOANNIS GIOVOS; PARASKEVI K. KARACHLE; IVONI FOURNARI – KONSTANTINIDOY; ELENI KYTINOU; YIANNIS ISSARIS; ERNESTO AZZURRO; LUCA CASTRIOTA; MANUELA FALAUTANO; et al. (Mediterranean Marine Science, 2020)
Here we present an update of the Mediterranean distribution of the lionfish Pterois miles, based on a comprehensive list of geo-referenced occurrences up to October 2019. New data were provided by multiple reporting tools and citizen science initiatives. Our findings suggest that well established populations of P. miles exist in the Levantine Sea, in the southern and central Aegean Sea, as well as in the Greek Ionian Sea, whilst so far, only a few individuals were reported from Tunisia and southern Sicily (Italy). We also argue about the future expansion of this invasive species in the Mediterranean region and about the role of climate change by projecting the limits of winter isotherms under different climate change scenarios. Under the assumption that the mean winter sea surface temperature is the main limiting factor of the range expansion of the species (i.e. 15.3oC winter isotherm), P. miles could substantially expand in the Mediterranean Sea, except the coolest northernmost regions, under future climatic scenarios. These results were discussed in comparison to published outcomes of species distribution modelling.